PENGENDALIAN CONVEYER BATUBARA SECARA WIRELESS - Syamsudin, Eko; Winata, Tony; Tanubrata, Ferry (Universitas Tarumanagara, 2008)
Since 1980’s wireless technology apply to communication, for example Handy talky and hand phone. This days wireless technology expand to world industry, there was introduce wireless communication use for control coal conveyer, this system can help operators work more easily. Many some of purpose can be added when implemented an automated control of coal conveyer. The conveyer were remotely and communicate with a wireless system that were decrease a human error at work.